2008
DOI: 10.1302/0301-620x.90b7.19918
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of blood flow in the rotator cuff using laser Doppler flowmetry

Abstract: The aim of this study was to define the microcirculation of the normal rotator cuff during arthroscopic surgery and investigate whether it is altered in diseased cuff tissue. Blood flow was measured intra-operatively by laser Doppler flowmetry. We investigated six different zones of each rotator cuff during the arthroscopic examination of 56 consecutive patients undergoing investigation for impingement, cuff tears or instability; there were 336 measurements overall. The mean laser Doppler flowmetry flux was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 31 publications
1
59
1
1
Order By: Relevance
“…4,19,30 However, since Codman 6 described a watershed area in the rotator cuff, there is debate as to whether there is a ''critical area'' of relative avascularity in the supraspinatus tendon, just proximal to its bony insertion, that makes it vulnerable to tendinopathy and eventual tears. 8,[17][18][19]22,28,30,34,35 The presence of a critical zone is primarily supported by in vitro studies. 8,18,19,28,30 Most of these studies involved injecting a hardening substance and analyzing resultant tissues by histologic techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,19,30 However, since Codman 6 described a watershed area in the rotator cuff, there is debate as to whether there is a ''critical area'' of relative avascularity in the supraspinatus tendon, just proximal to its bony insertion, that makes it vulnerable to tendinopathy and eventual tears. 8,[17][18][19]22,28,30,34,35 The presence of a critical zone is primarily supported by in vitro studies. 8,18,19,28,30 Most of these studies involved injecting a hardening substance and analyzing resultant tissues by histologic techniques.…”
mentioning
confidence: 99%
“…Recent studies using in vivo physiologic techniques, such as doppler ultrasound and laser doppler flowmetry (LDF), have failed to support the presence of a critical zone in the rotator cuff. 12,17,34,35 However, these studies were limited by small sample sizes and inefficient analyses. Also, the pattern of blood flow around a partial-thickness tear has not previously been studied as a separate group.…”
mentioning
confidence: 99%
“…9 In another study regarding the vascularity of torn tendons, it was found that there was a substantial increase in vascularity at the edges of rotator cuff tears. 10 This might reflect an attempt at repair.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, authors have described it as being hypovascular (Codman;Macnab, 1973;Lohr & Uhthoff, 1990;Brooks et al, 1992;Determe et al, 1996;Kane et al, 2006;Adler et al, 2008;Levy et al, 2008), avascular (Rathburn & Macnab;Herberts et al, 1981;Ling et al, 1990;Chansky & Iannotti) or hypervascular (Seitz et al) (Table I). Barr (2004) postulated avascularity to arise from the compression and attrition of the supraspinatus tendon in a narrowed subacromial space.…”
Section: Introductionmentioning
confidence: 99%